Kewenangan Penyidik Polri untuk Melakukan Penahanan Tersangka Pelaku Tindak Pidana dalam Proses Peradilan Pidana - Aris Munandar; I Gusti Agung Ngurah; Abu nawas (Syntax Literate, 2023)
In the criminal justice system, the police are the "gateway" for justice seekers. This is where things started. This initial position puts the police at a disadvantage. As an investigator the police must make arrests (when necessary) detentions, which means the police must have a strong suspicion that the person is the perpetrator of the crime. Detention can be done if it is deemed necessary. As stated in Article 1 Point 21 of the Code of Criminal Procedure: "Detention is the placement of suspects or defendants in certain places by investigators, public prosecutors, or judges with their determination in the case and in the manner provided for in this law. Based on the results of the study, the author concludes that legal considerations of police investigators are authorized to detain suspected perpetrators of criminal acts, because the National Police as investigators in the investigation process have duties and obligations of their main duties and functions. In connection with these duties and obligations, the police have the authority as stipulated in: 1) Law Number 8 of 1981 concerning the Code of Criminal Procedure, namely the condition of subjective detention is a condition stemming from the assessment and concern of the investigator that if the defendant is not detained then the accused will run away, will damage or eliminate evidence, and will even repeat the crime; 2) Law Number 2 of 2002 concerning the National Police of the Republic of Indonesia; and clearly about how the management of criminal investigations must be carried out by the police as stipulated in Perkapolri No. 14 of 2012 concerning Management of Criminal Investigations